AHAB AS CAPITALIST, AHAB AS COMMUNIST: REVISING MOBY-DICK FOR THE COLD WAR - Murphy, Geraldine (Surfaces, 1994)
Contrasting F.O. Matthiessen's and R.W.B. Lewis's interpretations of Moby-Dick and Melville's later novels (in American Renaissance and The American Adam respectively) with Richard Chase's revisionist rebuttal (in Herman Melville: A Critical Study), the author describes literary discourse on Melville as an important site, in American Studies, to exorcise the old left and redefine liberalism in the postwar period.